A Tale of Two More Metaphors: Storylines About Mathematics Education in Canadian National Media. Issue 4 (1st October 2016) - Chorney, Sean; Ng, Oi-Lam; Pimm, David
ABSTRACT: In this companion piece to the article "A Tale of Two Metaphors: Storylines About Mathematics Education in Canadian National Media" (this issue), we further explore constructed meanings through the use of positioning theory. In our examination of 71 articles in the two Canadian national newspapers ( The Globe and Mail and The National Post ), we focus primarily on communication acts and further our investigation into storylines and positionings concerned with mathematics education. Elaborating on aspects of two more metaphors, those of war and competition, we highlight the production of dichotomies and the shared aspect of taking sides. An investigation of the ramifications and effects that are brought to the fore in the articles we examined involves two general themes: the purpose of education and the point of mathematics education itself. We draw on David Labaree's framework identifying social efficiency and social mobility as different patterns of educational goals and highlight its parallels with the storylines in the articles we examined. The messages of the storylines feed the continued production of culturally shared narratives surrounding the purposes of mathematics education and education in general.